PENERAPAN MODEL TEAMS GAMES TOURNAMENT UNTUK MENINGKATKAN MOTIVASI BELAJAR KIMIA PESERTA DIDIK - Devi Putri Heryati; Eny Winaryati; Desiana Heryani (LitbangMu Jawa Tengah and Teacher Professional Education UNIMUS, 2024)
This study aims to increase student learning motivation in the chemistry learning in grade XII A-2 SMAN 15 Semarang using Teams Games Tournament learning model. This type of research is classroom action research according to Kemmis and McTaggart, which includes (1) planning stages, (2) action, (3) observation, and (4) reflection. The subjects in this study were XII A-2 grade students at SMAN 15 Semarang for the 2024/2025 school year, a total of 32 students. Data collection methods used in this study were observation and documentation. The instruments used in this study were student activity observation sheets and interview, directly or with questionnaires. Data analysis techniques using descriptive qualitative data analysis. The results showed that by providing student activity, the application of the Teams Games Tournament (TGT) learning model could increase student learning motivation in the chemistry learning process in grade XII A-2 SMAN 15 Semarang.